Impact of COIVD19 on our Ecology in India - Suresh K (Global Journal of Ecology - Peertechz Publications, 2020)
Various environmental factors influence the outbreak and spread of epidemic or pandemics which, in turn, can damage our environment. COVID-19 has been declared as a global health emergency - a pandemic on 13 March 2020 due to spread of corona virus. It's rapid onset, spatial expansion and complex consequences made it a once-in-a-century global disaster. It is affecting 213 countries and territories around the world as on 15 September 2020. Signs of growing inequality because of covid-19 can be detected from cities to countryside.  Major ecological impacts will be of three types: 1) a)Temporary improvement in air and water pollution due to lock down implemented to minimize the transmission of the infection, that led to cessation of all economic and production activities and vehicular movements. b) Temporary ergonomic challenges due to work from home (WFH) culture working long hours at home with no proper furniture's. c) Impact of long hours of screen-time leading to fatigue, redness, dryness in the eyes, headache, and behavioural issues, 2) Long term negative ecological impacts a) arising out of millions of masks, face shields, personal protective equipment (PPEs), surgical gloves needing disposal as they are generating massive amount of medical wastes coupled with poor Medical waste management capacities due to limited investments for the last few decades by the municipal authorities. b) increased demand on water and soap for frequent hand washing or side effects of sanitizers to be used. All these will lead to worsening of physical environmental situation such as shoreline pollution or increased smoke due to the unhygienic disposal of sanitary consumables and dead bodies. 3) Mental health has been emerging as one of the most important concerns since the beginning of the pandemic.  This article presents an early overview of the observed and potential impacts of the COVID-19 on the environment. I argue that the effects of COVID-19 are determined mainly by anthropogenic factors. Most Public Health Professionals opine that the impact of mitigating actions taken will continue to have on the future of ecology and the objective of Sustainable Development Goals by 2030. Materials & methodology: For this paper the National, State and City wise Covid-19 cumulative infection and death cases data were taken up to 15th September 2020 from the daily bulletins of the MOH&FW, GOI and the National Health Mission websites of State Governments {(https://www.mohfw.gov.in/) & https://covid19.karnataka.gov.in)} and www.health.economictimes, www.timesofIndia.com. Some of the reviews and reports in print media of various institutions working both on the Covid 19 and Ecology.  Study setting & sampling: The review covers major states and cities setting. Being the secondary data review available data was used with no sampling.